Projects for Ferme Ornée on the island of Lokrum by Archduke Ferdinand Maximilian of Habsburg - Marić, Mara; Ćorić, Franko; Obad-Šćitaroci, Mladen; Duić, Marin (2021)
This research deals with projects for a residence on the island of Lokrum by Archduke Maximilian I of Habsburg (1832-1867). In the short period of owning the island (1859-1867), Maximilian ordered three different designs for Lokrum. The subject of research in this paper is the first phase of the project, dating from 1860 to 1866, when the general plan of the island, Maximilian’s residence, farm building and court chapel were designed. The research is based on an analysis of primary archival sources while the contemporary models for the project have been found through literature review. Twenty archival drafts have been described textually and graphically published. Maximilian actively participated in the planning and design process, but the author of the projects was Thomas Friedrich. After the general plan of the island from 1860 came sixteen preserved plans of Maximilian’s residence, which are with this research dated to the period from 1862 to 1864. The drafts for the farm building, court chapel and altar date back to the period from 1864 to 1866. Although in terms of architecture it was only partially built (only the landscape part of the project was executed), the Lokrum project from 1860 to 1866 shows Maximilian’s original idea of the island before the later grandiose plans of transformation into an imperial residence.
Bibliografske bilješke uz tekst ; bibliografija i izvori: 53 jed.
Summary.
Keywords: Ladanjska arhitektura -- Ljetnikovci -- Projekti gradnje -- Prostorno planiranje -- Historicizam; Maksimilijan Habsburški; 19. st; Lokrum -- Dubrovnik